Umbilical cord blood markers of oxidative stress in pregnancies complicated by preterm prelabor rupture of membranes - Musilova, Ivana; Tothova, Lubomira; Menon, Ramkumar; Vlkova, Barbora; Celec, Peter; Hornychova, Helena; Kutova, Radka; Andrys, Ctirad; Stepan, Martin; Kacerovsky, Marian (The journal of maternal-fetal & neonatal medicine, 2016)
OBJECTIVE: To determine umbilical cord blood total antioxidant capacity (TAC), ferric reducing antioxidant power (FRAP), thiobarbituric acid-reacting substances (TBARS), advanced glycation end products (AGEs) and markers of oxidative stress in pregnancies complicated by preterm prelabor rupture of membranes (PPROM) and their associations with microbial invasion of the amniotic cavity (MIAC) and/or histological chorioamnionitis (HCA), funisitis and selected aspects of short-term neonatal morbidity. MATERIALS AND METHODS: One hundred and sixty-five women with singleton pregnancies complicated by PPROM were included in this study. Blood samples were obtained by venipuncture from the umbilical cord vein after the delivery of the newborn. The umbilical cord blood concentrations of TAC, FRAP, TBARS and AGEs were measured. RESULTS: The presence of MIAC, HCA and funisitis did not show differences in the umbilical cord blood TAC, FRAP, TBARS and AGEs concentrations. Positive correlations were found between the gestational age at sampling and umbilical cord blood TAC and AGEs concentrations (TAC: rho = 0.26; p = 0.001; AGEs: rho = 0.35; p < 0.0001). There was no association between umbilical cord blood TAC, FRAP, TBARS and AGEs concentrations and selected aspects of short-term neonatal morbidity. CONCLUSIONS: Oxidative stress is associated with PPROM, as indicated by the presence of markers tested in the umbilical cord blood; however, the evaluated oxidative stress markers are not influenced by the presence of MIAC and/or HCA, and funisitis or subsequent development of selected aspects of short-term neonatal morbidity.
Keywords: gestační stáří; dospělí; rupture of membranes; chorioamnionitida; Chorioamnionitis; Antioxidants; Female; Thiobarbituric Acid Reactive Substances; microbial invasion of the amniotic cavity; předčasný odtok plodové vody; biologické markery; oxidační stres; novorozenec; Gestational Age; Biomarkers; Advanced glycation end products; Adult; mladý dospělý; ženské pohlaví; fetální krev; Oxidative Stress; lidé; Infant, Newborn; Glycation End Products, Advanced; těhotenství; total antioxidant capacity; preterm delivery; histological chorioamnionitis; Fetal Membranes, Premature Rupture; Fetal Blood; thiobarbituric acid-reacting substances; prospektivní studie; Prospective Studies; Young Adult; antioxidancia; produkty pokročilé glykace; ferric reducing antioxidant power; Pregnancy; látky reagující s kyselinou thiobarbiturovou; Humans